Digital financial inclusion and income inequality in WAEMU: What causality for what heterogeneity? - Kolotioloman Soro; Melain Modeste Senou (Cogent Economics & Finance, 2023)
In developing countries, economic inequality is attracting considerable attention. Many factors including financial exclusion are key in explaining income gap in developing countries. This paper examines the effect of access to financial services through digital technologies on income inequality. Using data from the World Development Indicator (WDI), the Central Bank of West African States (BCEAO) and the Standardized World Income Inequality Database (SWIID), we estimated a pooled means group estimation (PMGE) and a dynamic fixed effect (DFE) as a robustness test. The results indicate that digital financial inclusion leads to a decrease in income inequality. In the long run, there is a negative and significant effect of digital financial inclusion on inequality. The short run results evidenced more of the heterogeneity effect of digital financial inclusion in WAEMU countries due to the diversity, inconclusiveness, and counterintuitive results of the effect of DFI on inequality.
Keywords: E24; H23; H53; H55; I32; I38; O15; 330; digital financial inclusion; heterogeneity; income inequality; WAEMU